Novel ways of enhancing the properties of natural materials. - Amorsolo, Alberto V., Jr.
Natural materials from plant, animal and ground sources have been useful to mankind since the dawn of civilization. However, the new generation of high technology products require materials with unusual combination of properties which become harder to find in natural materials. New and novel ways to overcome this limitation are therefore being devised to either significantly enhance the properties of these natural materials or transform them into hybrid structures with the desired combination of properties. These methods make use of the usual principle of changing the material property through a change of composition and/or structure (usually done at the microscale level). However, one of the breakthrough principles in creating a radically different set of materials from existing ones lies in reducing the physical dimensions of conventional materials to the nanomaterials appears to be major challenge for materials scientists and engineers of this century.
Keywords: Enhancement; Nanomaterials; Natural materials; Material properties